Pemodelan Principal Component Regression dengan Software R - Margaretha Ohyver (Bina Nusantara University, 2012)
Principal Component Regression (PCR) is one method to handle multicollinear problems. PCR produces principal components that have a VIF less than ten. The purpose for this research is to obtained PCR model using R software. The result is a model of PCR with two principal components and determination coefficients R(square) = 97,27%.